Candi Ratu Boko: Peninggalan Historis Awal Bersatunya Hindu-Budha Masa Jawa Kuno - Titah Pratyaksa, I Gede (PANGKAJA, 2012)
Ratu Boko temple situated in Orchard Dawung Bokoharjo village, Prambanan district, Sleman regency. Originally a magnificent building that was built during the reign of King Rakai Panangkaran, which is one of the descendants Wangsa dynasty in 745-784 AD This temple has Hindu elements. It can be seen from the Linga and Yoni, Ganesha statues, and gold plate that reads "Om Rudra ya namah swaha" as a form of worship of the god Rudra is another name of Lord Shiva. The existence of Hindu elements proved religious tolerance and religious spirituality integrated two forces that once thrived in Yogyakarta in ancient times. To preserve the Hindu heritage in the form of Ratu Boko, can not be separated from efforts to involve and empower local communities in tourism. Utilization of cultural remains or "Cultural Heritage" as a tourist attraction means indirectly the public, in this case Hindus, are invited to keep the Ratu Boko temple as a place of worship of Shiva-Buddha oldest in Indonesia. Keywords: Ratu Boko temple, Shiva-Buddhist, Hindu, Tourism